(untitled) (EU and comparative law issues and challenges series (ECLIC), 2019)
The recent initiative of the European Commission (hereinafter: EC) to empower consumer organisations to seek compensation on behalf of a group of consumers that have been harmed by an illegal commercial practice by way of introducing a Proposal of a Directive on representative actions for the protection of the collective interests of consumers and repealing the Injunctions Directive 2009/22/EC (hereinafter: the Directive Proposal), if successful, should mark a new era of collective redress at EU level. In the light of these developments, the paper will first present the background of the Proposal, the present state of EU collective redress mechanisms. It will focus on current issues, such as cross-border collective redress litigation in the context of Brussels I (Recast) Regulation. Namely, after the ‘Dieselgate’ scandal providing for efficient cross-border collective redress mechanisms at EU level has been recognized as one of the main regulatory challenges. Although at this point the outcome of the EC’s initiative is uncertain, the central part of the paper will evaluate the crucial aspects of the Proposal. The conclusion will address key findings and emphasize possible effects of the proposed changes on the future redress opportunities for EU consumers.